Crypto between the state and Sharia: Who has final authority? - Qutieshat, Enas; Al Adwan, Majed; Chami, Yassine; Muhtar, Mohamad Hidayat; Khater, Maya (Research Journal in Advanced Humanities, 2026)
This paper addresses the tensions caused by the intersection of state, Sharia, and the global market that arises due to the unique nature of cryptocurrencies. Historically, using cryptocurrencies challenges state control over the money supply and raises questions of compliance with Sharia, specifically the prohibitions of gharar (uncertainty) and maysir (gambling). The complexity of fatwas in this system has been overlooked by focusing primarily on them as isolated normative references with no connection to state regulations and market realities. This research views fatwas on the interoperability of digital markets and state authorities. The central research question is: how does Sharia-compliant governance of cryptocurrency in the Muslim world, combined with digital markets and state authorities, coexist with moral-religious principles and legal authority? The research hypothesizes three protagonists interacting in a triangular governance relationship: (1) fatwas represent ethical boundaries in the context of maqāṣid al-syarī‘ah; (2) the state represents a pro-active, positive religiously-oriented regulation; and (3) the market represents ethical compliance. The model of proposed co-regulation presents a robust conceptual synthesis of cryptocurrency and Sharia compliance theories with practical use for market operators, fatwa institutions, and religious policymakers, to develop a Sharia-compliant digital financial ecosystem.